Recommender algorithms as a source of power in contemporary society - Bojić, Ljubisa (Sociološki pregled, 2022)
Both tech companies and AI algorithms exercise immense power in today’s globally interconnected world, which is based on big data and digital footprints of online users. This paper analyses the transfer of power from societies to tech companies and algorithms with the aim of examining whether recommender algorithms can be considered a public good. Deployed methods include content analysis and literature reviews. The study has found that control exercised over public opinion, decisions and moods of online users is unprecedented to such a high degree in human history. The above-mentioned control is based on the impact of both tech companies and algorithms. The limitation of this research is the lack of quantitative analysis. Future research should concentrate on defining recommender algorithms as a public good and analyzing how different media content, including virtual reality, affects citizens’ psychology.
Keywords: techno-feudalism; Big Tech companies; AI based recommender algorithms; mass media; censorship